A study on distribution pattern of lower respiratory tract infections in children under 5 years in a tertiary care centre - S., Srinivasa; Patel, Shruthi (International Journal of Contemporary Pediatrics, 2018)
Background: Respiratory infections are the leading cause of mortality in children below 5 years in India as well as worldwide. 16% mortality in children below 5 years is attributed to lower respiratory tract infection. Various factors influence the occurrence of the disease like environmental factors, lack of immunization, malnutrition. Present study was conducted to know the distribution pattern of lower respiratory tract infections, common pathogens associated with respiratory infections and risk factors associated with it. Methods: This study was conducted in Department of Pediatrics, KIMS Bangalore for a period of 1 year from January 2016 to December 2016. Total of 172 children admitted to ward and ICU with history suggestive of respiratory infection were included in the study after excluding congenital heart problems, congenital lung problems and immunodeficiency state. Results: In the present study, male predominance (59.3%) was observed. The incidence of respiratory tract infection was 17.5%. The common pathogen isolated was streptococcus pneumoniae. Most common respiratory infections included bronchopneumonia followed by bronchiolitis, croup, and lobar pneumonia. The common symptoms were cough, fever and hurried breathing. Anemia was observed in majority of them. Conclusion: Respiratory infections if timely managed, the mortality associated with it can be reduced. Pneumonia is a major killer disease in children below 5 years in India. Understanding the symptoms and signs and time of referral to tertiary centre not only reduces the mortality but it also reduces morbidity. So, it is important to create awareness among the health care personnel regarding common age of presentation of various types of respiratory infection and warning sign.